The Sleepless Rider’s great dream - Churampi Ramírez, Adriana (2019)
Raymundo Herrera is the protagonist of the third novel of Manuel Scorza’s five-novel series about indigenous uprising. His insomnia and efforts to keep the cause alive make Herrera a disconcerting figure. Through his participation in the community’s history, from the 18th century onward, he symbolizes memory. His insomnia means he is able to observe the abuse suffered uninterruptedly, and he is moved to impel the community into recovering its land. He is not alone in his quest; other leaders, excluded from official history, ride with him in his attempt to return to the community their land, together with their time and history, which are written into the landscape. The theft of their land also threatens their collective memory and place in history. The Sleepless Rider’s mission evokes the concepts of territoriality and personal history so essential to any understanding of indigenous communities’ development.